EKSISTENSI DEKOMPOSISI RANK PADA MATRIKS ATAS ALJABAR MAX-PLUS TERSIMETRI - Suroto Suroto; Najmah Istikaanah; Sri Maryani (UPT Penerbitan Universitas Jember, 2022)
In this paper, we discuss the rank-decomposition in the symmetrized max-plus algebraic matrix. The existence of rank decomposition is shown using minor rank in the symmetrized max-plus algebra and a link among symmetrized max-plus algebra and conventional algebra. The result is a rank-decomposition in symmetrized max-plus algebraic matrix exists. Furthermore, the rank-decomposition is not unique. Keywords: Existence, link, rank decomposition, symmetrized max-plus algebra